1993
DOI: 10.1002/gcc.2870070102
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of chromosome 9 aberrations are associated with clinico‐pathologic subsets of non‐Hodgkin's lymphoma

Abstract: In this study we analyzed nonrandom aberrations affecting chromosome 9 in a series of 426 consecutively ascertained, karyotypically abnormal non-Hodgkin's lymphoma (NHL) tumors derived from 407 patients. Cytogenetic abnormalities were correlated with clinical, histologic, and immunologic features. Structural abnormalities of chromosome 9 were identified in 60 specimens derived from 59 patients. The recurring abnormalities among these were associated with 4 clinico-pathologic subsets. The first comprised 7 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 26 publications
(24 reference statements)
5
40
0
Order By: Relevance
“…56 The regions of minimal common 6q deletion vary with disease type, suggesting that different tumor suppressor genes might be affected in each of these neoplasms. [57][58][59] In BL cell lines these deletions are consistently associated with loss of heterozygosity in the 6q25-27 region. 56 Genes possibly affected by 6q abnormalities include BACH2 (encoding for B-lineage specific transcription factor, a putative tumor suppressor gene), on 6q15, 60,61 and BLIMP1 (B-lymphocyte maturation promoting), on 6q21-q22.1.…”
Section: Discussionmentioning
confidence: 99%
“…56 The regions of minimal common 6q deletion vary with disease type, suggesting that different tumor suppressor genes might be affected in each of these neoplasms. [57][58][59] In BL cell lines these deletions are consistently associated with loss of heterozygosity in the 6q25-27 region. 56 Genes possibly affected by 6q abnormalities include BACH2 (encoding for B-lineage specific transcription factor, a putative tumor suppressor gene), on 6q15, 60,61 and BLIMP1 (B-lymphocyte maturation promoting), on 6q21-q22.1.…”
Section: Discussionmentioning
confidence: 99%
“…[285][286][287] In hematologic malignancies, deletions involving the long arm of chromosome 6 are observed primarily in lymphoid malignancies, ie ALL, [288][289][290] lymphoproliferative disorders and NHL. 288,[291][292][293][294] These results indicate that the long arm of chromosome 6 harbors a yet uncharacterized tumor suppressor gene(s) that is altered in many tumors. Cytogenetic studies showed that chromosome 6q is also often affected in acute/lymphomatous ATLL.…”
Section: Other Candidate Tumor Suppressor Genes In Atllmentioning
confidence: 99%
“…Its expression is ubiquitous, and is greater in terminally differentiated tissues, suggesting a role for this kinase in specialized functions in the cell (Gran˜a et al, 1994). Cdk9 maps to chromosome 9q34.1 (Bullrich et al, 1995), a region involved in non-random chromosome alterations, such as T-cell non-Hodgkin's lymphomas, bladder tumors and several myeloproliferative disorders (Offit et al, 1993;Orlow et al, 1994). Cyclin partners of Cdk9 are members of the family of the T cyclins (T1, T2a and T2b) (Peng et al, 1998) and cyclin K (Fu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%